Asuhan Kebidanan Pada Bayi Baru Lahir Dengan Lilitan Tali Pusat Di Pmb Rungkut Surabaya - Nadya Amelia; Fauziah F. Hernanto (2025)
According to the World Health Organization (WHO), newborn or neonatal deaths account for 37% of all child deaths each year. As many as 8,000 newborn babies around the world die every day due to things that cannot be prevented, such as asphyxia caused by entanglement in the umbilical cord. Researchers found a case where the umbilical cord was wrapped around the baby's neck and arms with two coils of umbilical cord in Mrs. F's baby at midwifery clinic Rungkut Surabaya. Comprehensive midwifery care is one way that can help prevent complications from the first to the fourth stage of labour, new born and contraception. The aim of this Final Project Report is to provide comprehensive midwifery care during the first to fourth stages of labor and family planning counseling for Mrs. F to newborn baby Mrs. F with umbilical cord coil at midwifery clinic Rungkut Surabaya. This research method is descriptive and the type used is a case study. In this case, this is done by loosening the umbilical cord, then removing it from the baby's arms and head as soon as possible. During the birth process, the mother was able to cooperate and follow every instruction given by the midwife, the baby was born normally, the mother's physical condition was normal after an examination and an episiotomy was not carried out, then there was a grade 1 tear that occurred spontaneously when pushing. Examination of the mother after 2 hours of labor was conscious of compost mentis with no abnormal bleeding. Next, the researcher provides CEI regarding mobilization, nutrition, exclusive breastfeeding, postpartum danger signs, which the mother understands and hopes can be implemented by the client so that the mother and baby remain healthy.